Monosodium Glutamate(MSG) 사용이 소고기뭇국의 감각특성 및 소비자 기호도에 미치는 영향 - 정예지(Yehji Chung); 강민정(Minjeong Kang); 김다인(Dain Kim); 강진수(Jinsoo Kang); 하정헌(Jung-Heun Ha); 이영승(Youngseung Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구에서는 MSG의 감칠맛이 소고기뭇국의 감각특성과 소비자 기호도에 미치는 영향이 조사되었다. 소고기뭇국에서 MSG를 첨가함에 따라 단맛, 짠맛, 감칠맛, 고기맛이 유의적으로 증가하였고 신맛과 쓴맛은 감소하였다. 전반적 기호도가 가장 낮았던 소금 농도 0.35% 시료에 MSG 0.16%를 첨가한 결과, 가장 기호도가 높았던 0.50% 소금 농도(대조구)보다 전반적 기호도가 유의적으로 높게 나타났다. 이는 MSG 첨가에 의해서 시료의 기호도를 대조구와 동일 수준으로 유지하면서 30%의 나트륨 저감화의 가능성을 보여줬다고 할 수 있다. 또한, 소금 농도 0.35% 시료에 MSG 0.04% 이상을 첨가한 시료는 대조구와 비교했을 때 단맛이 2배가량 증가하였다. 그러나 본 연구는 소고기뭇국에 한정된 연구로 조리식품의 종류에 따라 MSG와 다른 감각특성 간 상호작용이 상이할 것으로 예상된다. 따라서 다양한 조리식품에 MSG를 적용하여 그에 따른 감각특성(짠맛, 단맛 등)과 소비자 기호도에 대한 연구가 지속해서 필요할 것으로 판단된다. The objective of this study was to investigate the effects of monosodium glutamate (MSG) on the sensory attributes and acceptability of beef and radish soup (Korean soegogi-muguk). A total of 200 consumers were used to evaluate samples containing various sodium (0.35∼0.50%) and MSG concentrations (0.01, 0.04, 0.16%). Consumer preference was assessed using a 9-point-hedonic scale while they were asked to check whether terms from a list applied to describe the sample and rate the intensity. Overall, the intensity of sweetness, saltiness, umami, and beef taste of samples increased with the addition of MSG while bitterness was suppressed. When 0.16% MSG was added to a sample with 0.35% salt that showed the lowest liking value, the acceptability was highest among samples tested. These findings indicated that it was possible to reduce sodium intake by 19% in beef-radish soup by adding MSG. In addition, the sample with 0.35% salt in the presence of 0.04% MSG was two times sweeter than the sample with 0.50% salt, suggesting that MSG exhibited a positive effect on sweetness of beef and radish soup. Overall, these results will benefit researchers who want to know the optimal level of MSG to reduce the amount of sodium or sugar used in beef and radish soup. KCI Citation Count: 5